Turkey - Tuzcu O.; Kaplankiran M.; Anil S.; Das S.; Oztürk A.; Tasdemir A.; Eraslan H.; Gülsen O.; Asil Yilmaz M.; Yesiloglu Y.; Yüzbas A.; Yurtmen M. (Improvement of the citrus sector by the setting up of the common conservation strategies for the free exchange of healthy citrus genetic resources, 2001)
Turkey